Default mode network changes in multiple sclerosis: a link between depression and cognitive impairment?. (16th September 2016) - Bonavita, S.; Sacco, R.; Esposito, S.; d'Ambrosio, A.; Della Corte, M.; Corbo, D.; Docimo, R.; Gallo, A.; Lavorgna, L.; Cirillo, M.; Bisecco, A.; Esposito, F.; et al.
Abstract : Background and purpose: In multiple sclerosis (MS), depression is a common disorder whose pathophysiology is still debated. To gain insights into the pathophysiology of depression in MS, resting‐state (RS) functional connectivity (FC) changes of the default mode network (DMN), salience network (SN) and executive control network (ECN) were assessed in a group of depressed MS (D‐MS) patients and in appropriately matched control groups. Methods: Sixteen D‐MS patients, 17 non‐depressed MS (ND‐MS) patients, 17 non‐depressed healthy controls and 15 depressed subjects (D‐S), age, sex and education matched, cognitively preserved and non‐fatigued, were enrolled. All participants underwent a neuropsychological evaluation and RS functional magnetic resonance imaging study. Results: Comparing D‐MS patients with D‐S, within the DMN, a significant RS‐FC suppression was found in the posterior cingulate cortex (PCC); comparing D‐MS with ND‐MS, FC was significantly increased in the anterior cingulate cortex and significantly reduced in the PCC. Within the SN increased FC in the right supramarginal gyrus and right middle frontal gyrus was found in D‐MS patients compared to D‐S and to ND‐MS; within the ECN increased FC in the right inferior parietal cortex was found in D‐MS patients compared to ND‐MS patients. Conclusions: In cognitively preserved D‐MS patients, FC derangement occurs in the SN, ECN and DMN. In the latter, changes occurring both in the anterior cingulate cortex and PCC suggest that depression in MS may be linked to MS itself and, in particular, to a peculiar pattern of network abnormalities favored by MS pathology through disconnection mechanisms. Reduced FC in the PCC, similar to MS patients with cognitive impairment, suggests a functional link between depression and cognitive impairment in MS.